EVALUATION OF URETEROSCOPIC PNEUMATIC LITHOTRIPSY FOR URETERAL STONES - Ihsan Ullah Khan (Journal of University Medical & Dental College, 2014)
ABSTRACT: OBJECTIVE: To evaluate success rate, auxiliary procedures and complications associated with ureteroscopic pneumatic lithotripsy of ureteric stones. PATIENTS AND METHODS: The study was conducted among 100 patients between May 2011 to July 2013. The mean age of the patients was 32 ± 3 years. Ureteroscopic pneumatic lithotripsy was performed using rigid Wolf ureteroscope and Swiss Lithoclast. Stone diagnosis and localization was done by C.T KUB without contrast. IVU was done in cases where indicated. Stone size range was between 0.6 cm to 2.0 cm with mild to marked obstructive changes in collecting system. All patients were having normal renal function tests. RESULTS: Majority of the patients 60/100 (60%) presented with lower ureter calculi, 28/100 (28%) presented with upper ureter calculi and 12/100 (12%) with middle ureter calculi. The patients were followed with plain X-ray KUB and USG for 2 months. Stone free status was declared as complete clearance of stone fragments from urinary tract. Overall success rate was 96%. Auxiliary procedures conducted include balloon dilatation of ureterovesical junction 67% and of upper ureteric stricture 1%, retrograde urography 1%, dormia basket manipulation 88% and D-J stent placement 87%. Complications encountered were mild transient hematuria 67%, stone fragments migration 4%, urosepsis 2%, and residual stone fragments 4%, D-J stent associated discomfort 33% and repeat procedure 2%. CONCLUSION: Ureteroscopic Pneumatic Lithotripsyis is effective and safe treatment modality with unremarkable complications for ureteric stones.